Multinational Business Finance / Fifth Edition - Eiteman David K; Stonehill Arthur I (Allyn And Bacon, 1988)
The International Financial Environment, Trends and Themes, The International Monetary System, Balance of Payments and Parity Conditions, Spot and Forward Markets, Futures and Options Markets, Foreign Exchange Risk Management, Forecasting Foreign Exchange Rates, Managing Economic Exposure, Managing Transaction Exposure, Managing Translation Exposure, Capital Markets and Financing Instruments, Global Financial Markets, Cost of Capital and Financial Structure, International Portfolio Diversification, International Banking and the International Debt Crisis, Trade Documentation: Letters of Credit and Drafts and Bills of Landing, Specialized Trade Financing: Export Credit Insurance and Forfaiting and Countertrade, Direct Foreign Investment Decisions, Direct Foreign Investment Strategy, Political Risk Management, Multinational Capital Budgeting, Management of Ongoing Operations, Current Asset Management, Performance Evaluation and Control, Glossary, Author and Subject Index.
The International Financial Environment, Trends and Themes, The International Monetary System, Balance of Payments and Parity Conditions, Spot and Forward Markets, Futures and Options Markets, Foreign Exchange Risk Management, Forecasting Foreign Exchange Rates, Managing Economic Exposure, Managing Transaction Exposure, Managing Translation Exposure, Capital Markets and Financing Instruments, Global Financial Markets, Cost of Capital and Financial Structure, International Portfolio Diversification, International Banking and the International Debt Crisis, Trade Documentation: Letters of Credit and Drafts and Bills of Landing, Specialized Trade Financing: Export Credit Insurance and Forfaiting and Countertrade, Direct Foreign Investment Decisions, Direct Foreign Investment Strategy, Political Risk Management, Multinational Capital Budgeting, Management of Ongoing Operations, Current Asset Management, Performance Evaluation and Control, Glossary, Author and Subject Index.